La práctica coral en la interpretación del canto popular, de las(os) estudiantes de quinto y sexto años de la escuela básica particular Siglo XXI de la ciudad de Loja. Periodo 2014-2015 - Jiménez Macias, María Fernanda (2016)
Underestimation of the benefits offered choral practice in educational institutions, is the fundamental idea with which part the present research, for this purpose, a general objective is to identify the benefits of choral practice for the correct interpretation arises the popular song of the students, fifth and sixth years of the Special Primary School "Siglo XXI" city of Loja, using Latin American repertoire, for which methods such as scientific, hermeneutical and statistical was used, and it was necessary to use techniques to define the population consisted of two officials who were applied a structured interview guide, 36 parents and 36 students who were assigned a survey giving a total of 74 people under investigation, the results obtained, the 100% state that the institution lacks a choir to represent it results that allow us to formulate an alternative proposal is the creation of a choral group with the fifth and sixth years. It is concluded that the lack of a choral group negatively affects students so because they do not have a space where they can develop their musical skills and therefore their creative intelligence, so it is recommended to authorities, teachers, parents, family and who make up the institution, support and sustain the creation of the choir for the development of musical artistic qualities of students.